The Classification of Relationship between Alumni Competence and Work Using Decision Tree Method - Rizqia Cahyaningtyas; Yasni Djamain Djamain; Nur Andhita Ramadanty (Sekolah Tinggi Teknik - PLN, 2021)
This study discusses the classification of the relationship between personal competence with work on the tracer study data of the PLN Institute of Technology. The results of the data from the alumni survey will be processed using a decision tree method that aims to provide information related to the relationship between personal competencies which have a very close relationship, close enough and not close to the work that the alumni get and become an evaluation material for the campus in the future. Where the decision tree method is one of the data mining classification methods that provides a tree structure that will serve as a decision tree. The tracer study data used from the graduation years of 2015, 2016, 2017, 2018 and 2019 are processed based on the year. And consists of 13 competency attributes and one competency that is used as a label or target. Based on the application of this method each year of graduation has a different level of accuracy based on the state of each data, for tracer study data 2015 graduation year accuracy of 56.03%, 2016 graduation data accuracy of 56.03%, while for tracer data the 2017 graduation year study was 78.90% accuracy, for the 2018 graduation study tracer data the accuracy was 52.94% and for the 2019 graduation tracer study data the accuracy was 40.12%.